THE GESNERIACEAE OF SULAWESI VI: THE SPECIES FROM MEKONGGA MTS. WITH A NEW SPECIES OF CYRTANDRA DESCRIBED - Abdulrokhman Kartonegoro; Daniel Potter (Research Center for Biology, 2014)
Field exploration of the flora of the Mekongga Mountainous area of Southeast Sulawesi was conducted from 2009 to 2011. Herbarium specimens collected during this exploration and additional collections from Herbarium Bogoriense (BO) included 21 species in nine genera of the family Gesneriaceae. These comprise one species of Aeschynanthus, four species of Agalmyla, one species of Codonoboea, seven species of Cyrtandra, one species of Epithema, three species of Monophyllaea, two species of Rhynchoglossum, one species of Rhynchotechum and one species of Stauranthera. Twelve of these species are consider-ed endemic to Sulawesi while the rest are known to occur on neighbouring islands or are more widely distributed. Monophyllaea merrilliana, previously known only from the Philippine Islands and Borneo, is newly recorded for Sulawesi. A new species of Cyrtandra collected in the Mekongga area, C. widjajae, which resembles C. gorontaloensis from North Sulawesi but differs in having shorter pedicels and curved rather than straight fruits, is described.